(untitled) (Research, Society and Development, 2021)
Objective: To build knowledge about Trichomonas vaginalis/trichomoniasis with male university students in the areas of Exact Sciences and Nature, Technology and Geosciences and Informatics of the Federal University of Pernambuco. Methodology: University Extension carried out through Health Education in the semesters 2017-2019. Was mounted stand with panels on T. vaginalis/trichomoniasis and with the aid of exposed countertops folders, booklets, condoms, intimate lubricants and laboratory material for trichomoniasis diagnosis. Sixty extensionists, undergraduate students of Biological Sciences, Health and Medical worked in the transmission and construction of knowledge. Result: Educational actions reached 3,162 students with mean age between 19-23 years. The dialogue was consolidated but at first some university students showed shyness and in general, declare not knowing the forms of transmission and treatment, the epidemiological importance of male sex in the maintenance of trichomoniasis as well as male health problems. In the actions about 3,500 folders on T. vaginalis/trichomoniasis and 15.000 leaflets/booklets on HIV/AIDS, syphilis and viral hepatitis, in addition to 25.000 penile condoms, 2.000 vaginal condoms and 40.000 sachets of intimate lubricant were distributed. Conclusion: The actions contributed to the participatory educational process where male university students acted as reflective and active subjects in the construction of knowledge about T. vaginalis/trichomoniasis and in the achievement of autonomy in the adoption of prevention, leading to the sustainability of healthy and safe sex life. The University is a strategic locu to promote innovative and transformative actions in Health Education that favor the training of its students as well as its link with society.